216k views
4 votes
9x-4=3x-28 step by step

1 Answer

2 votes

Answer:

Explanation:

9x-4= 3x-28

We simplify the equation to the form, which is simple to understand

9x-4=3x-28

We move all terms containing x to the left and all other terms to the right.

+9x-3x=-28+4

We simplify left and right side of the equation.

+6x=-24

We divide both sides of the equation by 6 to get x.

x=-4

User Richardaum
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.